2020
DOI: 10.1002/mus.26988
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2–associated Guillain‐Barré syndrome with dysautonomia

Abstract: Coronavirus disease 2019 , caused by severe acute respiratory coronavirus 2 (SARS-CoV-2), is associated with Guillain-Barré syndrome (GBS). [1][2][3][4][5][6][7][8] We describe a patient with quadriplegic GBS with dysautonomia preceded by mild COVID-19-induced diarrhea.A 72-year-old man with coronary artery disease, hypertension, and alcohol abuse presented to a tertiary hospital with symmetric paresthesias and ascending appendicular weakness. Seven days earlier he had mild diarrhea, anorexia, and chills, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 9 publications
1
67
0
3
Order By: Relevance
“…After the diagnosis of COVID-19, some GBS cases were admitted to the ICU [30,31,33,43]. Therefore, the correct and timely diagnosis of GBS associated with COVID-19 can prevent its progress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the diagnosis of COVID-19, some GBS cases were admitted to the ICU [30,31,33,43]. Therefore, the correct and timely diagnosis of GBS associated with COVID-19 can prevent its progress.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous immunoglobulin therapy was performed for all patients. • Decreased forces, MRC grade of 2/5 at proximal and 3/5 at distal lower limbs, and 4/5 in both arms • Deep tendon reflexes were absent in both legs and decreased to 1+ in the upper extremities 17 [43] • Symmetric paresthesias…”
Section: Guillain-barré Syndrome In Covid-19mentioning
confidence: 99%
“…Pascual-Goñi E et al [194] [63], [101], [191], [215], [218], [219], [220], [221], [222], [223], [224], [225], [226], [227], [228], [229] Abbreviation: M: Male, F: Female, NR: Not reported Abbreviation: M: Male, F: Female, NR: Not reported J et al [127], reported a 69-year-old woman with acute necrotizing myelitis. Optic Neuritis after COVID-19 was reported in only one patient.…”
Section: ] Sotocamentioning
confidence: 99%
“… EMG/NCS (day 13): prolonged right ulnar & bilateral tibial/peroneal motor distal latencies with slow conduction velocities, absent F waves, ↓ right ulnar/peroneal CMAP amplitudes, absent right ulnar/bilateral sural SNAPs, normal EMG with poor effort, overall suggestive of demyelination. IVIG (0.4 g/kg/day for 4 days) Poor, prolonged ICU (> 1 month) stay ( Su et al, 2020 ) Bursa, Turkey 53, F 3-day history of dysarthria associated with progressive weakness and numbness of the lower extremities 3-day history of dysarthria associated with progressive weakness and numbness of the lower extremities Three-day dysarthria & progressive lower limbs weakness & numbness, & areflexia No symptoms prior, mild fever (day 5 after neurological symptoms) Admission: mild neutropenia, normal electrolytes, LFT, RFT & CRP. Day 5: mild lymphocytopenia, ↑ CRP, positive COVID-19 nasopharyngeal swab.…”
Section: Neurologic Manifestationsmentioning
confidence: 99%